2022
DOI: 10.1021/jacs.2c00922
|View full text |Cite|
|
Sign up to set email alerts
|

Suppressing Immune Responses Using Siglec Ligand-Decorated Anti-receptor Antibodies

Abstract: The sialic acid-binding immunoglobulin-type lectins (Siglecs) are expressed predominantly on white blood cells and participate in immune cell recognition of self. Most Siglecs contain cytoplasmic inhibitory immunoreceptor tyrosine-based inhibitory motifs characteristic of inhibitory checkpoint co-receptors that suppress cell signaling when they are recruited to the immunological synapse of an activating receptor. Antibodies to activatory receptors typically activate immune cells by ligating the receptors on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“… 90 Finally, conjugating Siglec ligands to an anti-receptor antibody can be used to suppress the excessive immune response in specific immune cells. 91 Although only synthetic Siglec-9 agonists were tested in virus-related inflammatory settings, such approaches are promising tools for reducing inflammation during viral infections.…”
Section: Siglec-sialic Acid Interactions In Mediating Hyper-inflammationmentioning
confidence: 99%
“… 90 Finally, conjugating Siglec ligands to an anti-receptor antibody can be used to suppress the excessive immune response in specific immune cells. 91 Although only synthetic Siglec-9 agonists were tested in virus-related inflammatory settings, such approaches are promising tools for reducing inflammation during viral infections.…”
Section: Siglec-sialic Acid Interactions In Mediating Hyper-inflammationmentioning
confidence: 99%
“…Studies have shown that coengagement of a Siglec receptor with the high affinity IgE receptor (FcεRI) on the surface of mast cells results in robust inhibition of mast cell activation and anaphylaxis. 5,12 Siglec-3 (CD33) is expressed on the surface of mast cells and basophils and its endogenous ligand is α2,3 sialyllactose and α2,6 sialyllactose�both of which form the basis of the structures made here. GlycoCAP could be used to install clickable azido-sialoglycans onto allergen, which would engage allergen-specific IgE attached to FcεRI.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Lectins are glycan-binding receptors that represent a promising class of therapeutic targets. Sialic acid-binding immunoglobulin-like lectins (Siglecs) are one example of a lectin family that has shown particular promise as targets in treating allergic inflammation and preventing anaphylaxis. Siglecs are transmembrane receptors that bind sialic acid-containing glycans and are differentially expressed on immune cells such that each immune cell has its own Siglec expression profile. Most, but not all, Siglecs have immune suppressive activity by virtue of possessing cytoplasmic immunoreceptor tyrosine-based inhibitory motifs that recruit phosphatases . Therefore, Siglecs not only offer an avenue for immune cell inhibition but also provide an approach for cell-specific targeting.…”
Section: Introductionmentioning
confidence: 99%
“…129 Paulson and his coworkers developed an antibody connected siglec ligand that targeted immune cells via anti-IgD/E antibody and inhibited unwanted immune cell activation. 130 This work defined a new idea of antibody–drug conjugates. Ohmae coated poly(sarcosine)-block-poly( l -lactic acid) (lactosome) with sialic acid monosaccharides and oligosaccharides to prevent accelerated blood clearance (ABC) via interaction with Siglec-E.…”
Section: Multivalent Sialic Acid Materials For Biomedical Applicationmentioning
confidence: 99%